Improvement of Organic Matter and Nutrient Removal from Domestic Wastewater by Using Intermittent Hydraulic Rates on Earthworm-Microorganism Biofilters - Villamar-Ayala, C (IWA Publishing, 2020)
Biofilters based on earthworms-microorganisms represent, particularly in developing countries, an interesting alternative for domestic wastewater treatment due to their easy operation and low cost. However, there are several operational aspects that should be better understood in order to improve their performance. This paper studies the effect of using intermittent hydraulic loading rates to improve organic matter and nutrient removal from domestic wastewater using these biofilters. Three laboratory-scale columns, operating at a 2.5 m3 m2 day1 hydraulic loading rate, were used. The B1-24 h, B2-8 h, B3-4 h column loading rates indicate that the columns were operated continuously for 24, 8 and 4 h, respectively. Each column (biomass biofilm/earthworms, redox potential, and head loss) and its corresponding operational performance parameters (TCOD, NH4þ, NO3, NO2, TP) were monitored. The results showed that the B2-8 h intermittent hydraulic loading rate results in the best global performance, with 74%, 57%, and 20% average removal efficiencies for TCOD, nitrogen, and phosphorus, respectively. Moreover, it showed the best biomass growth (biofilm and earthworms), activity (as redox potential changes) and the lowest clogging effects (up to 1.0 cm). The intermittent operation influences the behavior of the earthworm-microorganism biofilters and offers the possibility of optimizing its global performance and achieving a resilient technology. © 2020 The Authors Water Science & Technology